Temporal Trends in Percutaneous Coronary Intervention Appropriateness: Insights From the Clinical Outcomes Assessment Program. Issue 1 (7th July 2015) - Bradley, Steven M.; Bohn, Chad M.; Malenka, David J.; Graham, Michelle M.; Bryson, Chris L.; McCabe, James M.; Curtis, Jeptha P.; Lambert-Kerzner, Anne; Maynard, Charles
Abstract : Background—: It is unknown whether the appropriate use of percutaneous coronary intervention (PCI) has improved over time and whether trends in PCI appropriateness have been accompanied by changes in the use of PCI. Methods and Results—: We applied appropriate use criteria to determine the appropriateness of all 51 872 PCI performed in Washington State from 2010 through 2013. We evaluated the number of PCIs performed from 2006 through 2013 to provide a comparator period that preceded statewide appropriateness assessment beginning in 2010. Between 2010 and 2013, the overall number of PCI decreased by 6.8% (13 267 PCIs in 2010 to 12 193 in 2013) with a 43% decline in the number of PCIs for elective indications (3818 PCIs in 2010 to 2193 PCIs in 2013). The decline in the use of elective PCI was significantly larger after the onset of statewide PCI appropriateness assessment in 2010 ( P =0.03). The proportion of elective PCIs classified as appropriate increased from 26% in 2010 to 38% in 2013, whereas the proportion of inappropriate PCIs decreased from 16% to 13% ( P <0.001 for trends). Significant improvements in the proportion of inappropriate PCI were limited to the tertile of hospitals with the largest decline in PCIs classified as inappropriate (25% in 2010 to 12% in 2013; P =0.03). Conclusions—: In Washington State, the use of PCI for elective indications has decreased over time with concurrent improvements in PCI appropriateness. However, improvements in PCI appropriateness were limited to a minority of hospitals. Understanding processes at these high-performing hospitals may inform efforts to improve PCI appropriateness. Abstract : Supplemental Digital Content is available in the text.